Structural chemistry of metal coordination complexes at high pressure - Schröder, Martin (Elsevier, 2014)
The application of pressures of up to about 10 GPa may induce significant geometric, configurational, conformational and packing changes in molecular solids. This review highlights and describes recent advances in high pressure studies of coordination complexes, many of which have been conducted at synchrotrons or other central facilities. The main focus is on the wide range of geometric changes which occur with pressure. In some cases these changes have associated physical effects, and the review describes materials exhibiting negative linear compressibility, spin cross-over phenomena, magnetism and molecular conduction, as well as detailing the exciting possibilities for future developments in this area of research.